2006
DOI: 10.1097/01.cad.0000231484.17063.9a
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of BH3-only proapoptotic proteins in mitochondrial-dependent Phenoxodiol-induced apoptosis of human melanoma cells

Abstract: Phenoxodiol is a chemically modified analogue of the plant hormone isoflavone with antitumour activities. In the present study, we have examined its ability to induce apoptosis in human melanoma cells and the mechanisms involved. Apoptosis was observed in Phenoxodiol-treated cells by using annexin V/propidium iodide staining and determining mitochondrial membrane potential. To determine which caspase pathways were involved in Phenoxodiol-induced apoptosis, studies were performed using specific caspase inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
2
24
0
1
Order By: Relevance
“…As shown in Figure 3(A), 10-30 µM CTN directly induced a ∼ 7-18-fold increase in the intracellular ROS content of ESC-B5 cells, compared with untreated control cells. Since the protein expression ratio of Bax versus Bcl-2 is relevant to the mitochondria-dependent apoptotic pathway [30,31], with high and low Bax/Bcl-2 ratios associated with lower and higher apoptotic thresholds respectively, I determined whether CTN induced apoptosis via modulation of the Bax/Bcl-2 ratio. Immunoblotting revealed that CTN treatment of ESC-B5 cells caused the Bax and Bcl-2 expression levels to increase and decrease respectively ( Figure 3B), and densitometric analysis confirmed that CTN-treated ESC-B5 cells had a higher Bax/Bcl-2 ratio, which is indicative of apoptosis ( Figure 3C).…”
Section: The Effects Of Ctn On Esc-b5 Cellsmentioning
confidence: 99%
“…As shown in Figure 3(A), 10-30 µM CTN directly induced a ∼ 7-18-fold increase in the intracellular ROS content of ESC-B5 cells, compared with untreated control cells. Since the protein expression ratio of Bax versus Bcl-2 is relevant to the mitochondria-dependent apoptotic pathway [30,31], with high and low Bax/Bcl-2 ratios associated with lower and higher apoptotic thresholds respectively, I determined whether CTN induced apoptosis via modulation of the Bax/Bcl-2 ratio. Immunoblotting revealed that CTN treatment of ESC-B5 cells caused the Bax and Bcl-2 expression levels to increase and decrease respectively ( Figure 3B), and densitometric analysis confirmed that CTN-treated ESC-B5 cells had a higher Bax/Bcl-2 ratio, which is indicative of apoptosis ( Figure 3C).…”
Section: The Effects Of Ctn On Esc-b5 Cellsmentioning
confidence: 99%
“…1,2 Phenoxodiol has been referred to as a pan-cancer drug, 3 causing apoptosis in cancer cell lines and murine cancer models via both intrinsic and extrinsic pathways. [4][5][6][7][8][9][10][11][12][13][14] Plasma membrane electron transport (PMET) has been shown to be a target of phenoxodiol in several studies with cancer cell lines. 3,13,15 PMET consists of an outer membrane (surface) NADH-oxidoreductase, redox-recycling plasma membrane ubiquinone and an inner membrane NADH-oxidoreductase.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that a number of flavonoids (quercetin, apigenin, myricetin) known for their capacity to inhibit proteasome activity (28) would be able to induce apoptosis by enhancing Noxa expression. In addition, Noxa upregulation was reported to be associated with the proapoptotic effects of several polyphenols such as resveratrol, phenoxodiol or tetramethoxystilbene as well as the flavonoid isoliquiritigenin (37)(38)(39)(40). Therefore, such a family of natural specific Noxa upregulators might be useful for the development of novel combining therapeutic protocols in CLL.…”
Section: Discussionmentioning
confidence: 99%